Testi, discorsi e «istituzioni sociali». Una nozione saussuriana al vaglio della semantica contemporanea - De Angelis, Rossana (Rivista Italiana di Filosofia del Linguaggio, 2014)
Ferdinand de Saussure proposes to consider language as a system and as an institution. These concepts represent respectively the relational and social nature of language, and they have gone through contemporary linguistic theories. According to Saussure’s theory, language is a social institution different from other ones as policy, law, etc. However, language is always in relationship with them, sharing the same social dimension concerning a specific linguistic community. Then to analyse linguistic objects we have to consider also this relationship. Following the concept of social institution proposed by Saussure, we can observe how the social dimension of language has been integrated in contemporary linguistic theories. First used by Louis T. Hjelmslev in his essays about meaning, this concept reveals different semantic approaches. In particular, it allows to analyse the relationship between language and other institutions as constitutive of meaning, as in Michel Pêcheux’s discursive semantics and in François Rastier’s interpretative semantics.